PENERAPAN MEDIA PEMBELAJARAN GOOGLE SITES PADA MATERI LARUTAN PENYANGGA UNTUK HASIL BELAJAR SISWA : PENERAPAN MEDIA PEMBELAJARAN GOOGLE SITES PADA MATERI LARUTAN PENYANGGA UNTUK HASIL BELAJAR SISWA - Siti Zakina; Yunita, Luki; Aini Nadhokhotani Herpi (ALOTROP, 2025)
[The Application of Google Sites Learning Media on Buffer Solution Material for Student Learning Outcomes] This study aims to examine the application of Google Sites learning media on buffer solutions for student learning outcomes. The studyused a quasi-experimental method with a nonequivalentcontrol group design involving 66 12th grade students at SMAN 87 Jakarta. The research instrumentwas a multiple-choice test that had been validated through expert assessmentand empirical testing. Data analysis was performed using descriptive statisticsand an independent t-test to identify differences in learning outcomes betweenthe two groups. The results showed that the average post-test scoreof the experimental class (90.27) was higher than that of the control class (82.15) becauselearning using Google Sites provided access to materials that were moreinteractive, structured, and easier for students to understand. The independent t-testproduced a sig value (2-tailed) <0.0001, indicating a significant differencebetween the two classes. Thus, the application of Google Siteswas very effective in improving student learning outcomes on buffer solution material.  Keywords: Learning Outcomes; Buffer Solution; Google Sites.